Structural study of 2-hydroxyethyl cellulose (2HEC) solid biopolymer electrolyte doped with NH4Br: effect on ionic conductivity - M. N. Faeqah; M. I. H. Sohaimy; N. H. Ahmad; M. Muthuvinayagam; M. I. N. Isa (Springer Science and Business Media LLC, 2025)
Indexed